2020
DOI: 10.1002/nau.24523
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing voiding experiences of men choosing seated and standing positions

Abstract: Voiding positions and preferences in men are not well characterized. In this study, we aim to understand the interplay of voiding characteristics and their impact on voiding position. Methods: We designed a 27-item survey to assess voiding characteristics and lower urinary tract symptoms (LUTS) severity in men seen in urology and other outpatient clinics. Participants included adult men patients and adult men accompanying patients at our institution's outpatient clinics. Data collected included demographics, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Consequently, they revelaed that the preferred voiding position was largely associated with physical limitations. However, the participants did not state differences for stream quality between both position 11 . Last but not least, researchers from Japan compared a series of voiding positions in normal males; they indicated that Qmax was highest in the prone position, followed by standing, sitting, supine, and the lateral positions 5 …”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Consequently, they revelaed that the preferred voiding position was largely associated with physical limitations. However, the participants did not state differences for stream quality between both position 11 . Last but not least, researchers from Japan compared a series of voiding positions in normal males; they indicated that Qmax was highest in the prone position, followed by standing, sitting, supine, and the lateral positions 5 …”
Section: Discussionmentioning
confidence: 97%
“…Similarly, another study stated that uroflowmetry should always be performed in the preferred position 7 . Thus, the most comfortable position should be chosen for voiding in uroflowmetry 1,8,11,17 . Hence, we only included participants whose natural voiding position was standing and excluded the effect of other voiding positions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations